2020
DOI: 10.1007/s12325-020-01390-2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial De-Escalation in the ICU: From Recommendations to Level of Evidence

Abstract: Antimicrobial de-escalation (ADE) is a component of antimicrobial stewardship (AMS) aimed to reduce exposure to broad-spectrum antimicrobials. In the intensive care unit, ADE is a strong recommendation that is moderately applied in clinical practice. Following a systematic review of the literature, we assessed the studies identified on the topic which included one randomized controlled trial and 20 observational studies. The literature shows a low level of evidence, although observational studies suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“… 33 Besides, although the microbiology laboratories’ role and rate of antimicrobial cultures per patient varied widely among the hospitals surveyed, none of them appears to have used the culture results and AST data for de-escalation of the antibiotic therapies, as recommended to reduce detrimental effects on patients as well as to minimize the development of AMR. 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 Besides, although the microbiology laboratories’ role and rate of antimicrobial cultures per patient varied widely among the hospitals surveyed, none of them appears to have used the culture results and AST data for de-escalation of the antibiotic therapies, as recommended to reduce detrimental effects on patients as well as to minimize the development of AMR. 34 …”
Section: Discussionmentioning
confidence: 99%
“…33 Besides, although the microbiology laboratories' role and rate of antimicrobial cultures per patient varied widely among the hospitals surveyed, none of them appears to have used the culture results and AST data for de-escalation of the antibiotic therapies, as recommended to reduce detrimental effects on patients as well as to minimize the development of AMR. 34 All the above could represent a common scenario associated to the recurrent identification of MDR E. coli and ESKAPE pathogens in the hospitals surveyed, as well as in other Mexican hospitals. 16,17,35,36 We consider that our findings could be partly explained by the absence of formally established ASPs in the hospitals surveyed.…”
Section: Resistant Escherichia Coli and Eskape Pathogens Were Frequently Identified In The Hospitalsmentioning
confidence: 93%
“…In fact, many authors have attempted to define and classify the ecological effects linked to the administration of different antibiotics [ 54 , 55 ]. However, the proposed classification was based on experts’ opinion and seemed to be influenced by regional epidemiological resistance data [ 6 ]. Moreover, as far as we know, despite the large number of studies suggesting the safety of de-escalation [ 56 , 57 , 58 ], its ecological benefits and effects on intestinal microbiota and on MDRO acquisition have never been demonstrated [ 6 ].…”
Section: The Effect Of Antibiotics On the Microbiota Is A Complex Phenomenonmentioning
confidence: 99%
“…However, the proposed classification was based on experts’ opinion and seemed to be influenced by regional epidemiological resistance data [ 6 ]. Moreover, as far as we know, despite the large number of studies suggesting the safety of de-escalation [ 56 , 57 , 58 ], its ecological benefits and effects on intestinal microbiota and on MDRO acquisition have never been demonstrated [ 6 ]. More surprisingly, in a recent literature review aiming to identify risk factors associated with the acquisition and emergence of CRE, the authors suggested a correlation between the use of carbapenems and the high risk of acquisition.…”
Section: The Effect Of Antibiotics On the Microbiota Is A Complex Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation